2019
DOI: 10.17569/tojqi.592046
|View full text |Cite
|
Sign up to set email alerts
|

Developing EFL Learners’ Speaking and Oral Presentation Skills through Pecha Kucha Presentation Technique

Abstract: The goal of this study is to examine the potential of Pecha Kucha presentation style for English language learners who are prospective teachers of English. The participants were students enrolled in an advanced-level speaking course in the English language teaching department of a state university in Turkey between 2016 and 2018. Students were required to make presentations in Pecha Kucha format, a fast-paced, time-constrained presentation technique. As part of the study, 102 students completed an open-ended s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
3
5
0
Order By: Relevance
“…In terms of the use of technology, this study employed Blackboard to facilitate deliver of the intervention program, which may have helped improve students' performance [15]. This result accords with previous studies that used technology to improve students' speaking and presentation skills, employing a multimedia approach [51][52][53][54][55][56][57].…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…In terms of the use of technology, this study employed Blackboard to facilitate deliver of the intervention program, which may have helped improve students' performance [15]. This result accords with previous studies that used technology to improve students' speaking and presentation skills, employing a multimedia approach [51][52][53][54][55][56][57].…”
Section: Discussionsupporting
confidence: 76%
“…First and foremost, the researchers aimed to draw as much as possible from the existing literature on the procedures used in the current study to improve EFL students’ oral presentation skills. This research is aligned with Solmaz [ 56 ] in considering “the long-term character of the development process of oral presentation skills, described as central professional skills” (p.16). Moreover, the purpose of the study corresponds to Bandura’s view that social cognitive theory is particularly well adapted to explaining the evolution of complex behavior, such as oral presentation skills [ 19 ].…”
Section: Methodssupporting
confidence: 61%
See 2 more Smart Citations
“…Looking at an EAP context, Demirkol et al (2021) indicated that giving speeches and asking and answering questions in conferences were the most difficult task for undergraduate learners in EMI universities. In addition to those studies that had a more experimental nature, for instance, looking at the role of extensive reading (Yakut, 2020), the use of Pecha Kucha technique (Solmaz, 2019), the use of L1 (Yüzlü & Atay, 2020), as well the effect of pressured online planning (Tuzcu & Yalçın, 2020) on L2 learners’ speaking and pronunciation, researchers have also adopted a more naturalistic approach to examine the ways in which EFL teachers promoted extended student talk (Gümüşok & Balıkçı, 2020) and provided oral corrective feedback (Ölmezer-Öztürk & Öztürk, 2016). Based on natural classroom observations, Kemaloğlu-Er and Özata (2020), for instance, revealed codeswitching in group work to be a builder of solidarity and a means of task achievement and interactional fluency.…”
Section: Classroom Processes and Instructional Practicesmentioning
confidence: 99%